A THEORETICAL PERSPECTIVE ON THE THERAPEUTIC ROLE OF CHILDREN'S FOLK SONGS - Loredana Muntean (Különleges Bánásmód, 2020)
Starting from the idea that treating a problem is done more efficiently when we address the causes that generated it than when dealing with symptoms, respectively from theories that claim that most of the mental disorders have their roots in the mother-child relationship developed in the early childhood, through the paper entitled A Theoretical Perspective on the Therapeutic Role of Children's Folk Songs we intend to argue the more use of songs from children's folklore in music therapy. Thus, in the first part of the paper, we bring to the attention of the main theories that demonstrate the importance of the mother-child relationship from the early childhood in order to a healthy evolution of the child from the point of view of its psychic development, with special emphasis on their expression through vocal singing. In the second part of the study, we propose to approach the defense mechanisms from the perspective of the positive functions that it performs in the case of normal persons, as a defense mechanism and defense behavior. In the third part of the paper, we present an analysis of the repertoire of songs from the children's folklore from the perspective of the content of ideas, of the structure of the melodic line, of the specific rhythms, as a mirror of the relationships that children develop with themselves and with others, in particular with my mother. In the fourth part of the paper, we argue the use of songs from children's folklore in music therapy in order to trigger certain memories from the first childhood so that the traumas that have not been overcome are then treated properly. The paper concludes with some final considerations.